Hysteresis effects in electron guns - Agafonov, A.V.; Lebedev, A.N. (Вопросы атомной науки и техники, 2004)
Computer simulations of beam formation in an electron gun with large compression of a thin annular beam show some hysteresis effects: a beam with different currents can exist in the same external conditions. The results of computer simulation are presented for several simple drift and diode geometry and for the gun with large compression of an annular beam. Physics reasons of such behaviour are discussed.